Team IHMC at the 2020 Cybathlon: a user-centered approach towards personal mobility exoskeletons - Brandon Peterson; Mark Daniel; Vishnu Subra Mani; Brooke Arnold; Travis Craig; Jeremy Gines; Carlos Gonzalez; William Howell; Brandon Shrewsbury; Matthew Bellman; Peter Neuhaus; Robert Griffin (Journal of NeuroEngineering and Rehabilitation, 2022)
Abstract Background The past few decades have seen rapid advancements in exoskeleton technology, with a considerable shift towards applications involving users with gait pathologies. Commercial devices from ReWalk, Ekso Bionics, and Indego, mainly designed for rehabilitation purposes, have inspired the development of many research platforms aimed at extending capabilities for use as safe and effective personal mobility devices. The 2016 Cybathlon featured an impressive demonstration of exoskeletons designed to enable mobility for individuals with spinal cord injury, however, not a single team completed every task and only two completed the stairs. Major improvements were showcased at the 2020 Cybathlon, with seven of the nine teams completing a similar set of tasks. Team IHMC built upon its silver-medal success from 2016 with an upgraded device, Quix. Methods Quix features several notable improvements including an additional powered degree of freedom for hip ab/adduction to laterally shift the device and reduce user effort while walking, custom-tailored cuffs and soft goods based on 3D body scans to optimize user comfort, and a streamlined testing pipeline for online tuning of gait parameters. Results Team IHMC finished in fourth place behind the teams from EPFL and Angel Robotics. Although we suffered from a considerably slower flat-ground walking speed, our pilot reported marked improvements in overall effort, comfort, and ease-of-use compared to our previous device. Conclusions Clear progress in exoskeleton development has been exhibited since the inaugural Cybathlon, with tasks involving rough terrain, stairs, and ramps now posing little threat to most of the competitors. As a result, the layout of the powered exoskeleton course will likely undergo significant modifications to further push the devices towards suitability for personal everyday use. The current tasks do not address the issue of donning and doffing, nor do they simulate a scenario similar to maneuvering a kitchen to prepare a meal, for example. An additional limitation that may be more difficult to test in a competition setting is the required upper-body effort to manipulate the device in an effective manner.